Experimental investigation on cycle time in machining of forged crankshaft. (2021) - Pal, Sunil; Saini, Surendra Kumar
Abstract: Crankshaft is one of the most important component used in automobiles industries. Work study is an effective technique used to enhance the productivity of crankshaft manufacturing industry. It identifies the problems in terms of production time, number of processes and production rate. In present work, machining cycle time for forged crankshaft is investigated using work measurement method. It observed that machining time was more on two machining operations specifically in rough turning and grinding. Initial cycle time was 92.73 min for processing of crankshaft. After modifications, cycle time is reduced 88.63 min. It is found that machining cycle time is reduced by 4.1 min. This results in the improvement of cycle time by 4.42%. Further initial and final cost of machining is compared that is reduced 7%.